KANDUNGAN GIZI PADA DAUN DAN RIZOMA Enhalus acoroides DI PULAU BADAK BADAK KOTA BONTANG KALIMANTAN TIMUR - Muhammad Fahrul Rizal Setiawan; Lily Inderia Sari; aditya_irawan irawan (Jurnal Perikanan Unram, 2024)
The research aims to determine the nutritional content in the leaves and rhizomes of Enhalus acoroides from Badak Badak Island, Bontang City. The analysis of nutritional content uses proximate test analysis in the form of ash, fat, protein and carbohydrate content. The distribution characteristics of water quality and basic substrate based on stations used the Principal Component Analysis approach. The substrate texture at Stations AU and BT is clayey sand, while Station CB is sandy loam. The ash content in the rhizomes is lower than in the leaves with a ratio of 1:1.36. The lipid content in rhizomes is lower than in leaves with a ratio of 1:1.23. The protein content in rhizomes is lower than in leaves with a ratio of 1:1.23. The carbohydrate content in leaves is lower than in rhizomes with a ratio of 1:1.17.